Albumin Apheresis for Artificial Liver Support: In Vitro Testing of a Novel Filter. Issue 4 (16th May 2018) - Piatek, Tomasz; Giebultowicz, Joanna; Rüth, Marieke; Lemke, Horst‐Dieter; Bonn, Florian; Wroczynski, Piotr; Hrenczuk, Marta; Malkowski, Piotr; Rozga, Jacek
Abstract: Currently there is no direct therapy for liver failure. We have previously described selective plasma exchange therapy using a hemofilter permeable to substances that have a molecular mass of up to 100 kDa. The proof‐of‐concept studies and a Phase I study in patients with decompensated cirrhosis demonstrated that hemofiltration using an albumin‐leaking membrane is safe and effective in removing target molecules, alleviating severe encephalopathy and improving blood chemistry. In this study a novel large‐pore filter for similar clinical application is described. The performance of the filter was studied in vitro; it was found to effectively remove a wide spectrum of pathogenic factors implicated in the pathophysiology of hepatic failure, including protein bound toxins and defective forms of circulating albumin. Data on mass transport characteristics and functionality using various modes of filtration and dialysis provide rationale for clinical evaluation of the filter for artificial liver support using albumin apheresis.